Review of bamboo-feeding leafhoppers of the genus Mukaria (Hemiptera: Cicadellidae: Deltocephalinae) in China, with description two new species - Zhao, Yong-Tao; Luo, Qiang; Yang, Lin; Chen, Xiang-Sheng (Zootaxa, 2024)
Two new species, Mukaria creagra Zhao, Luo & Chen sp. nov. and Mukaria striola Zhao, Luo & Chen sp. nov., of the bamboo-feeding leafhopper genus Mukaria Distant, 1908 are described and illustrated form Guizhou and Yunnan, China. Three species moved from Mukaria Distant, 1908 into Mukariella Viraktamath & Webb, 2019. A key for all known Chinese species of Mukaria and Mukariella is given.